2019
DOI: 10.1016/j.colsurfb.2019.06.041
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of double network hydrogel of poloxamer-heparin/gellan gum for bone marrow stem cells delivery carrier

Abstract: In this study, a double network hydrogel of a natural polysaccharide gellan gum (GG) hydrogel and a synthetic hydrogel poloxamer-heparin (PoH) hydrogel (PoH/GG DNH) is introduced to complement disadvantages of each hydrogel and improve the microenvironment for cell delivery. The microstructure, surface morphology, gelation temperature, swelling and weight loss, sol fraction, mechanical property and thermal stability was examined. The potential of the composite hydrogel for cell vehicle was demonstrated by enca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
28
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 71 publications
2
28
0
Order By: Relevance
“…In another study, GG/poloxamer-heparin (PoH) hydrogel was used as a carrier for bone marrow stem cell (BMSCs) delivery, in that experiment, they prepared a double network of GG hydrogel composed of PoH as a matrix platform for stem cell cultivation. They found that the hydrogel supported cell adhesion, distribution ( Figure 5), and ECM production in an in vivo model [65]. Shin et al [38] used GG/Silk fibroin (SF) for the chondrogenic differentiation ability of BMSCs, using miR-30.…”
Section: Gellan Gum Cell Adhesion Propertiesmentioning
confidence: 99%
See 1 more Smart Citation
“…In another study, GG/poloxamer-heparin (PoH) hydrogel was used as a carrier for bone marrow stem cell (BMSCs) delivery, in that experiment, they prepared a double network of GG hydrogel composed of PoH as a matrix platform for stem cell cultivation. They found that the hydrogel supported cell adhesion, distribution ( Figure 5), and ECM production in an in vivo model [65]. Shin et al [38] used GG/Silk fibroin (SF) for the chondrogenic differentiation ability of BMSCs, using miR-30.…”
Section: Gellan Gum Cell Adhesion Propertiesmentioning
confidence: 99%
“…Major routes for preparing gellan gum-based biomaterials[4,32,[34][35][36][37][38][39][65][66][67][68][69].…”
mentioning
confidence: 99%
“…The DNH system was tested on bone marrow stem cells isolated from rabbits (rBMSCs) revealing that supported cell survival, maintained cell's morphology and phenotype. The in vivo results have demonstrated that PoH/GG DNH endorse the cell distribution, adherence, and ECM production [173].…”
Section: Graft-copolymerizationmentioning
confidence: 90%
“…The BMSCs were obtained following the previous reported study. (Choi et al, 2019) Briefly, the legs were extracted, and soft tissues were removed. The bones were rinsed with a 1.5% penicillin/streptomycin (PS, Gibco, Big Cabin, OK, USA) diluted in PBS.…”
Section: Methodsmentioning
confidence: 99%